Business start-up in Malaysia: Motivations, obstacles, government support and demographic-related traits (Journal of Business Management and Accounting, 2012)
Entrepreneurship is becoming increasingly important in today’s world due to its effectiveness and applicability in a country’s economic development. In this regards, many developed and developing countries are investing maximum resources and efforts to promote entrepreneurship. To achieve the goal, policy makers as well as economic stakeholders are playing their roles in promoting entrepreneurship. This includes educational institutions emphasising on motivating fresh graduates to choose entrepreneurship as their future career. Therefore, the purpose of this study is to highlight the factors that resist and encourage fresh graduates to choose and set up their own business. This paper categorises four factors namely demographic, motivational, challenges of obstacles and government support. This paper proposes that motivational factors such as family security, independence, intrinsic and extrinsic rewards influence fresh graduates’ decision to choose and set up a new business. With reference to challenges, this paper highlights that a lack of finance, complicated processes involved in setting up a business, high rate of taxes and duties, poor business infrastructure resist fresh graduates to dabble into entrepreneurial activities. This paper also points out that demographic factors like gender, previous experience and family background do influence fresh graduates’ decision to choose and set up a new business. In addition, this paper explains that government support in terms of providing business assistances like microfinance schemes, business-friendly system, low rate of taxes and duties. Easy business-related rules and regulations also encourage fresh graduates to choose and set up a new business. Finally, the paper proposes few propositions based on the previous literature and invites any researcher to empirically test them in order to further strengthen the entrepreneurship literature.